Silibinin protects Staphylococcus aureus from UVC-induced bactericide via enhanced generation of reactive oxygen species. Issue 53 (30th June 2017) - Cai, Jia-Yi; Wang, Yuan-Yuan; Ma, Kai; Hou, Yong-Na; Li, Jian; Yao, Guo-Dong; Liu, Wei-Wei; Otkur, Wuxiyar; Hayashi, Toshihiko; Itoh, Kikuji; Tashiro, Shin-ichi; Ikejima, Takashi
Abstract : ROS produced by silibinin suppresses UVC-induced Staphylococcus aureus cell death. Abstract : Silibinin is a major bioactive component of silymarin extracted from the milk thistle Silybum marianum . Silibinin has therapeutic potential for a wide variety of applications including anticancer, hepatoprotective and antiinflammatory medicines. There are studies reporting that silibinin has shown anti-bacterial effects, but its underlying mechanism has not yet been elucidated. In the present study, UVC inhibited growth of S. aurues in a dose-dependent manner and up-regulated production of reactive oxygen species (ROS). Silibinin treatment improved the survival of S. aureus in the presence of UVC. Interestingly, silibinin further enhanced the generation of ROS and activities of antioxidant enzymes (catalase (CAT) and glutathione peroxidase (GSH-PX)). To determine the role of ROS induced by silibinin, the scavengers ( N -acetylcysteine (NAC), glutathione (GSH) and superoxide dismutase (SOD)) or donors ( t BHP and H2 O2 ) of ROS were used to treat the bacterial cells. The results showed that ROS scavengers down-regulated the protective effect of silibinin, while ROS donors up-regulated it. Therefore, ROS produced by silibinin protects S. aureus cells from UVC-induced cell death. Our findings revealed novel insights into the relationship between silibinin, bacteria and ROS. Elucidation of the relationship will contribute to the development of important applications for further use of natural products, particularly for therapeutic strategies for S. aureus -associated diseases.